Comparative physical chemical stability of composition systems of hydroxyapatite/polyethyleneglycol 400 and 6000 in biological media - Boshytska, N.V.; Protsenko, L.S.; Budilina, O.N.; Kaplunenko, N.V.; Uvarova, I.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Interaction of composite systems on the bases of hydroxyapatite and polyethylene glycol (HAP + PEG) with molecular weights of 400 and 6000 with physiological Ringer and Ringer-Locke solution of NaCl has been investigated. By the methods of chemical analysis, it is established that the HAP + PEG 400 composite system interacts with biological media liberating calcium from a material step-by-step. The powder HAP + PEG 6000 system remains chemically stable during 100 h. By IR-spectroscopy, it is demonstrated that the spectrogram of surfaces of HAP + PEG 400 and HAP + PEG 6000 samples after the interaction with physiological solutions during 100 h contains valence vibrations in a range corresponding to the PEG presence. It can be supposed that the chemical activity of HAP + PEG 400 material relative to calcium and the prolonged presence of polyethylene glycol in the biological media help a reduction in both mineral metabolism and nervous impulses at bone defects. It is shown that the composite HAP + PEG 400 system is promising for the future development of materials for orthopedic applications.